A construção do agrário-ambiental no e do MST: o assentamento Mário Lago como síntese de um projeto em construção - Aquino, Manuela Martins da Costa (Universidade Federal de São Carlos, 2024)
This thesis has as its main objective to analyze the agrarian-environmental construction of the Landless Rural Workers Movement, understanding that this Movement develops an original conception of environmental issues in its articulation with the agrarian issue. We start from these two major themes: the environmental issue and the agrarian issue, understanding that they are a constituent part of Brazilian history, a history marked by plunder and violence, specifically in its appropriations through the development of the capitalist mode of production. But, also, in understanding a history of struggle and resistance. More than the option of not addressing these themes separately, we intend to carry out this construction and dialogue between them based on the MST. We start from the understanding that we cannot exclude land and its use as one of the constituent elements of the accumulation through the spoliation of natural assets. To bring concrete questions to the investigation, we analyzed the Mário Lago settlement as an integral part of the agrarian-environmental conception in and of the MST. It was chosen due to its location in the municipality of Ribeirão Preto - SP, a city considered a reference for the success of agribusiness, with a preponderance of the sugar and alcohol sector, and because it is the first in São Paulo that had its expropriation marked by environmental issues, specifically related to Guarani aquifer. We hypothesize that for families organized in the MST, the struggle for land is a totality that encompasses demands for fair access to land, water, and natural assets. Thus, both the incorporation of the environmental issue and the agrarian issue arise primarily from the experience of struggle, from what landless families are confronted with in their practical experience of fighting for land. This experience begins to be elaborated theoretically and is incorporated by the movement not only on a theoretical level but in its programmatic content of agrarian reform. Our final understanding is that the MST has its elaboration on the agrarian-environmental issue, which articulates theoretical and practical issues. However, it is still under construction, which is characteristic of a collective subject that is in movement.
The construction of the agrarian-environmental project in and of the MST: the Mário Lago settlement as a synthesis of a project under construction
Keywords: Acumulação por espoliação; Agrário-ambiental; Bens naturais; Movimento dos Trabalhadores Rurais Sem Terra; Accumulation through spoliation; Agrarian-environmental; Natural assets; Landless Rural Workers Movement; CIENCIAS HUMANAS::SOCIOLOGIA